Macro–Microscale Research on the Single Shear Characteristics of the Root–Loess Interface in Robinia pseudoacacia - Qi Gu; Bo Hong; Qiangbing Huang; Xiaosen Kang; Dengfei Zhang; Xiaopeng Guo; Gang Liu; Tao Xiao (Agronomy)
Rainfall-induced weakening of the root–loess interface’s shear strength is a key factor in slope instability, yet research on its shear characteristics remains limited. This study classifies Robinia pseudoacacia roots into three types (0–2 mm, 2–5 mm, and 5–10 mm) based on field surveys and 3D laser scanning. Large-scale, direct shear tests and three-dimensional failure surface reconstruction were conducted using a self-developed apparatus to examine the effects of water content (5%, 12%, and 19%), root type, and root content ratio (2.11%, 1.17%, and 0.23%) on shear strength and failure morphology. Results indicate that increasing water content reduces shear resistance, while root type and content ratio enhance cohesion. Shear resistance follows an order: Type II > Type III > Type I, influenced by root curvature, and increases with root content. A novel correlation is identified between shear strength and the fractal dimension of the failure surface. This study proposes a self-locking and interlocking mechanism based on micromechanical force chains between roots and soil particles, offering new insights into root–loess interface mechanics and a theoretical basis for evaluating vegetative root reinforcement under rainfall conditions.